Tracheostomy – The forgotten difficult airway?. (April 2017) - McGrath, Brendan A.; Haley, Daniel
Abstract: The demographics and clinical characteristics of patients with tracheostomies and laryngectomies are evolving. Many will have encounters with medical, nursing and allied healthcare staff from a variety of backgrounds and leadership can be expected from those with an interest or expertise in airway management. Recurrent themes have been identified that lead to harm for this vulnerable group, whilst at the same time, others have demonstrated that educational programmes and infrastructure adaptations can improve care. We highlight the steps that all airway specialists can take to influence the quality and safety of care that we provide in our institutions. Highlights: Tracheostomies are performed in increasingly complex patients, subsequently cared for by diverse multidisciplinary teams. Recurrent themes associated with care are well documented. Exemplar institutions have demonstrated improvements in the safety and quality of care for this vulnerable group. Organisations such as the Global Tracheostomy Collaborative bring together resources and methods to improve care. Airway experts are well placed to lead local, national and international quality improvements.